The Relocation of Indonesia's Capital: Public Policy Analysis and Its Implications for Regional Development - Dhavan Kusumo Wibowo; Syamsul Hadi (Eduvest - Journal of Universal Studies, 2024)
The relocation of the Indonesian capital has become a significant topic of debate in Indonesian public policy. In analyzing public policy and its implications, this study explores the factors that influenced the government's decision to move the country's capital. Using a multidisciplinary approach, this study considers the geopolitical, economic, social, and environmental aspects associated with the relocation process. The implications of this policy are also examined, including its impact on national development, the distribution of political power, as well as people's welfare. This research aims to provide a deeper understanding of the process of relocating Indonesia's capital and evaluate its impact on society and the country as a whole.